2022
DOI: 10.3389/fphar.2022.845018
|View full text |Cite
|
Sign up to set email alerts
|

Three-Day Continuous Oxytocin Infusion Attenuates Thermal and Mechanical Nociception by Rescuing Neuronal Chloride Homeostasis via Upregulation KCC2 Expression and Function

Abstract: Oxytocin (OT) and its receptor are promising targets for the treatment and prevention of the neuropathic pain. In the present study, we compared the effects of a single and continuous intrathecal infusion of OT on nerve injury-induced neuropathic pain behaviours in mice and further explore the mechanisms underlying their analgesic properties. We found that three days of continuous intrathecal OT infusion alleviated subsequent pain behaviours for 14 days, whereas a single OT injection induced a transient analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Oxytocin, on the other hand, plays a crucial role in controlling the GABA developmental polarity shift in pups during labor [ 8 , 9 , 10 ]. Similar to the UVN model, the nerve injury model also induces the downregulation of KCC2, and recently, in this model, Ba et al demonstrated in adult mice that the continuous infusion of oxytocin for three days increased KCC2 expression and function [ 40 ]. Based on our behavioral results, if oxytocin restored KCC2 expression in the ipsilesional vestibular nuclei, then allopregnanolone would enhance the inhibitory action of GABA, leading to a worsening of the syndrome and delayed vestibular compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin, on the other hand, plays a crucial role in controlling the GABA developmental polarity shift in pups during labor [ 8 , 9 , 10 ]. Similar to the UVN model, the nerve injury model also induces the downregulation of KCC2, and recently, in this model, Ba et al demonstrated in adult mice that the continuous infusion of oxytocin for three days increased KCC2 expression and function [ 40 ]. Based on our behavioral results, if oxytocin restored KCC2 expression in the ipsilesional vestibular nuclei, then allopregnanolone would enhance the inhibitory action of GABA, leading to a worsening of the syndrome and delayed vestibular compensation.…”
Section: Discussionmentioning
confidence: 99%